Mathematical modeling of handmade recycled paper drying kinetics and sorption isotherms - Vieira,M. G. A. (2008)
The objective of this work is to analyze and compare the natural and forced convective drying of handmade recycled paper. Drying of recycled cellulose pulp was carried out under laboratory environment conditions and in a convective dryer with forced air circulation and controlled conditions of air temperature and velocity. The tests were conducted following a two-factor central composed factorial design of experiments, with six runs at the central point. The drying results were analyzed and fitted to mathematical models of Fick, Henderson and Pabis (Ficks modified equation), Page and He (considering the nonlinear Fick effect). The model of Page represented best the experimental data and the one of Henderson and Pabis resulted in an adequate fit for the paper drying kinetics. Sorption isotherms were determined for the dried paper and the models of GAB (Guggenheim-Anderson-de Boer) and GDW (Generalised DArcy and Watt) resulted in excellent fits of the experimental data. The water sorption mechanism was suggested by the analysis of the calculated parameters of the GDW model.